2013
DOI: 10.1002/btpr.1829
|View full text |Cite
|
Sign up to set email alerts
|

MALDI‐TOF characterization of hGH1 produced by hairy root cultures of Brassica oleracea var. italica grown in an airlift with mesh bioreactor

Abstract: Expression systems based on plant cells, tissue, and organ cultures have been investigated as an alternative for production of human therapeutic proteins in bioreactors. In this work, hairy root cultures of Brassica oleracea var. italica (broccoli) were established in an airlift with mesh bioreactor to produce isoform 1 of the human growth hormone (hGH1) as a model therapeutic protein. The hGH1 cDNA was cloned into the pCAMBIA1105.1 binary vector to induce hairy roots in hypocotyls of broccoli plantlets via Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…It also has a lower operating cost than other types of bioreactors and has the advantage of easy scale-up for large-scale plant cell culture (Huang and McDonald 2012 ). Because of these advantages, López et al ( 2014 ) and Corbin et al ( 2016 ) used bioreactor cultures for recombinant protein production. However, there have been no reports on the use of bioreactors for the production of sweet proteins, such as miraculin.…”
Section: Introductionmentioning
confidence: 99%
“…It also has a lower operating cost than other types of bioreactors and has the advantage of easy scale-up for large-scale plant cell culture (Huang and McDonald 2012 ). Because of these advantages, López et al ( 2014 ) and Corbin et al ( 2016 ) used bioreactor cultures for recombinant protein production. However, there have been no reports on the use of bioreactors for the production of sweet proteins, such as miraculin.…”
Section: Introductionmentioning
confidence: 99%
“…Brassica oleracea var. Italica hairy roots carried pCAMBIA1105.1 binary vector accumulated isoform 1 of the human growth hormone (hGH1) in case of cultivation in 1.5-Litter mesh airlift bioreactor (López et al, 2014). The content of hGH1 7.8 ± 0.3 μg/g DW was for the bioreactor.…”
Section: Cultivation Of Hairy Roots In Bioreactorsmentioning
confidence: 99%
“…An isoform of human growth hormone was produced in Brassica oleracea hairy root cultures. The B. rapa hairy root cultures showed that the recombinant protein is characterized by highly homogeneous post translational profiles enabling a strong batch to batch reproducibility and highlighting the high homogeneity of the production system [180,181]. Although the recombinant proteins are accumulated or secreted by hairy root cultures in large quantities, proteins are degraded by the proteolytic activity of peptidases.…”
Section: Heterologous Protein Production In Roots/tubersmentioning
confidence: 99%